Rethinking global political economy : emerging issues, unfolding odysseys - Tétreault, Mary Ann, 1942- (Routledge/RIPE series in global political economy. Routledge/RIPE studies in global political economy, 2003)
Innovative approaches to the fundamental issues of the global political economy, in particular post Cold War development, analyses of capital and negative aspects of globalization.